Health and Nutritional Status of Hill Farm Women of Mandi District, Himachal Pradesh - Gupta, Radhna; Gupta, Rakesh K.; Choudhary, Preeti; Rana, Vaishnavi (Indian Journal of Extension Education, 2020)
Health and nutritional status of hill farm women selected from three blocks of Mandi District of Himachal Pradesh was assessed in the present investigation. Majority of selected farm women were in age group of 25-35 years and belonged to farm families having small to marginal land holdings. Mean height and weight of respondents was recorded below standards when compared at national level. Majority of farm women were ofmesomorph body type (75%) followed by endomorphic (18.33). Physical fitness rating of the respondents showed that 48.33 per cent had high average rating followed by 18.33 per cent having good fitness. Assessmentof nutritional deficiencies through clinical assessment revealed that majority of the respondents showed deficiency of iron and B complex vitamins. Less than 35 per cent women exhibited iron deficiency symptoms when assessedclinically. Comparison with suggested dietary intake revealed that the women had low intake for all food groups except sugar and oils. Their diets were inadequate in energy, protein, calcium, iron, B vitamins and ascorbic acid when compared with RDA.